A crônica e sua função pedagógica no contexto de sala de aula - Bonfim, Elismar Tavares (Universidade Federal do Tocantins, 2023)
The present work aims to expose the experience and results obtained with the theoretical research and analysis of the chronicle "Laços de Família" by the author MoacyrScliar. The following theorists, FREIRE, (2011); SILVA, (1999); CANDIDO, (1989); FERREIRA, (2008); SOLÉ, (1998); FISCHER, (2013); ROSENDO, (2015). In this way, we discuss the importance of pedagogy in teaching and also in the training of people / children and adolescents, the importance of studies of textual genres in the classroom, more specifically the chronicle that allows in the training of the student, a more critical and thinking.